Jamaica : Interim Staff Report Under Intensified Surveillance. (IMF Staff Country Reports; Country Report, 2005)
This paper reviews the Interim Staff Report Under Intensified Surveillance for Jamaica. The authorities have reaffirmed their objective of balancing the budget in FY 2005/06, while recognizing that this now poses a greater challenge. The IMF staff now estimates that measures in the range of 2.5-3.0 percent of GDP would be required to meet this goal, compared with the IMF staff's estimate of 1.7 percent of GDP at the time of the 2004 Article IV consultation. The room to maneuver in monetary and exchange rate policy remains constrained by the debt overhang.